Electrochemical behavior for corrosion protection of mild steel (MS) in 1M HCl medium by using lidocaine drug as an inhibitor - Ali H. Adel; El Aziz Fouda S. Abd; Tilp H. Amal (Zaštita Materijala)
The impact of Lidocaine as a save corrosion inhibitor for mild steel (MS) in 1M HCl by using weight loss (WL), Hydrogen evaluation (HE), open circuit potential (EO C P), potentiodynamic polarization (PP), electrochemical impedance spectroscopy (EIS) and Electrochemical frequency modulation (EFM) techniques has been investigated. Weight loss studied at various temperatures between (25-45oC) but Hydrogen evaluation and electrochemical studies at room temperature. The effect of temperature on the inhibition of corrosion has been studied and the thermodynamic activation and adsorption parameters were calculated. The morphology of MS was examined by scanning electron microscope with energy dispersive X-ray spectroscopy (SEM-EDX) technology and atomic force microscopy (AFM). EIS data indicate that in the presence of drug the double layer capacitance was decreased and the charge transfer resistance increased. The adsorption of the Lidocaine on MS surface was found to obey Langmuir adsorption isotherm and elucidate the mechanism of corrosion inhibition. The Lidocaine drug acts as mixed type inhibitor. All surface examination confirms the formation thin film covered the surface of the metal and prevent the surface of the metal from corrosion.